MARCH: factors associated with weight loss in patients with newly diagnosed type 2 diabetes treated with acarbose or metformin - Na Wang (Termedia Publishing House, 2019)
Introduction In this secondary analysis of the Metformin and AcaRbose in Chinese as the initial Hypoglycaemic treatment (MARCH) trial, we evaluated what demographic and clinical factors were associated with reduction in weight. We also assessed the effects of acarbose and metformin treatment on weight reduction.